Hubungan Penurunan Vitamin C Sayuran Hiperakumulator Dengan Residu Zat Aktif Insektisida Fipronil - Agus Sutanto; Hening Widowati; Mia Cholvistaria (Politeknik Negeri Lampung., 2021)
The use of insecticides is often unavoidable in the production of vegetable crops, but on the other hand it can lead to the presence of harmful substances in vegetables. In this regard, the aims of this study is to determine the relation of Insecticides active substance i.e fipronil toward the reduction of Vitamin C in Hyperaccumulator vegetable i.e Spinach (amaranthus hybridus), Caisim (Brassica juncea) and Kangkung (ipomea raptans) with ex pose facto method, and the samples taken by Completly Random Design (CDR) and tested in Laboratory. The regression test results show the sig value of 0.07> 0.05, the R square value of 0.871 means that it has a significant correlation with the percentage of the correlation of 87.10% on the decrease in vitamin C in vegetables. Vitamin C acts as an antioxidant to ward off free radicals. Insecticide Active Substances made the contains of vitamin in hyperaccumulator vegetable tissue being decrease. Based on the research conducted, it was concluded that there was a negative relationship between the residue of the active substance of the insecticide fipronil and a decrease in vitamin C in hyperaccumulator vegetables, in other words, when the residue of the active substance of the insecticide fipronil increased, the vitamin C content in the vegetables decreased.